Vitamin D and chronic kidney disease: mechanisms, clinical implications, and future perspectives - Wang, Hong; Yuan, Tingting; Wu, Weihua; Ou, Santao (Frontiers in Medicine, 2025)
BackgroundVitamin D deficiency is common in chronic kidney disease (CKD). Vitamin D/vitamin D receptor (VDR) signaling intersects inflammation, oxidative stress/mitochondrial injury, fibrogenic pathways, the renin–angiotensin–aldosterone system (RAAS), and the gut–kidney axis, providing a biologic rationale for renoprotection.MethodsNarrative review; literature identified from PubMed/MEDLINE, Embase, Web of Science, and Cochrane Library (January 2000–August 2025). Adult CKD populations (non-dialysis, dialysis, transplant) were included. Outcomes covered biologic/surrogate (e.g., proteinuria, estimated glomerular filtration rate [eGFR] slope) and hard endpoints (kidney failure, major cardiovascular events, fractures, mortality).ResultsNutritional vitamin D reliably corrects deficiency and improves laboratory profiles; VDR activators (VDRAs) suppress secondary hyperparathyroidism (SHPT). However, consistent benefits on hard outcomes have not been demonstrated across CKD settings, likely reflecting heterogeneity (baseline vitamin D status, stage, co-therapies, endpoints) and formulation/dosing differences (D₃ vs. D₂; cholecalciferol vs. calcifediol; steady vs. bolus). Safety considerations (hypercalcemia/mineral imbalance) apply to active agents and high-dose bolus regimens.ConclusionA pragmatic approach is warranted: replete deficiency with nutritional vitamin D (prefer D₃; consider calcifediol when faster repletion or persistent SHPT is relevant), avoid mega-bolus dosing, and reserve active VDRAs for clear SHPT indications with careful calcium–phosphate–parathyroid hormone (PTH) monitoring—rather than positioning vitamin D as disease-modifying therapy for unselected CKD. Future trials should enrich truly deficient, higher-risk phenotypes, standardize regimens, and prioritize event-driven hard endpoints with embedded mechanistic markers to confirm on-target biology.